2016
DOI: 10.1371/journal.pntd.0005253
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analyses of Individual Strongyloides stercoralis (Nematoda: Rhabditoidea) Provide Insights into Population Structure and Reproductive Life Cycles

Abstract: The helminth Strongyloides stercoralis, which is transmitted through soil, infects 30–100 million people worldwide. S. stercoralis reproduces sexually outside the host as well as asexually within the host, which causes a life-long infection. To understand the population structure and transmission patterns of this parasite, we re-sequenced the genomes of 33 individual S. stercoralis nematodes collected in Myanmar (prevalent region) and Japan (non-prevalent region). We utilised a method combining whole genome am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 33 publications
3
45
2
Order By: Relevance
“…An approach similar to a previous S . stercoralis population study [ 46 ] was used to analyze the whole genome data. In brief, raw reads were trimmed with skewer [ 50 ] (version 0.1.123; -q 30 -Q30 -l 60).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An approach similar to a previous S . stercoralis population study [ 46 ] was used to analyze the whole genome data. In brief, raw reads were trimmed with skewer [ 50 ] (version 0.1.123; -q 30 -Q30 -l 60).…”
Section: Methodsmentioning
confidence: 99%
“…Recent comparative analyses of the mitochondrial locus cytochrome c oxidase subunit 1 ( cox 1) [ 6 , 36 , 38 , 45 ] and the whole genome sequence of 33 individual S . stercoralis from Japan and Myanmar [ 46 ] indicated that there is substantial genetic diversity among S . stercoralis isolated from human hosts and [ 38 ] suggested that there might exist human- and dog-specialized subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Strongyloides genotyping surveys Barratt et al (2019b) and Jaleta et al (2017). This scheme was expanded here to include haplotype XV of 18S HVR-I (GenBank Accession: MT436714), identified in genomes sequenced from Japanese humans by Kikuchi et al (2016). For the purposes of this study, note that the haplotypes originally defined after the description of Barratt and colleagues were split into smaller segments as shown here.…”
Section: Rationale For Study Designmentioning
confidence: 99%
“…Genetic analysis has shown that there are genotypic variations in S. stercoralis populations and global diversity. There are two lineages of S. stercoralis , termed type A and type B 3 . Type A causes infections in humans and dogs, while type B infects only dogs 4 .…”
Section: Introductionmentioning
confidence: 99%